Bridging Linguistic Gaps through Translation of COVID-19 Terms from English into Albanian - Flett, Dorjana Klosi (European Scientific Journal, ESJ, 2025)
During the critical period of the global COVID-19 outbreak, Albania, like many other nations, faced the urgent need to communicate vital public health information effectively. The selection of appropriate terminology was paramount to ensuring that the public understood the nature of the virus, the measures necessary to prevent its spread, and the overall health strategies implemented by the government. Henceforth, this study aims to identify the COVID-19 terminology used by the Albanian Health Authorities to describe the virus and to analyse the strategies employed in translating these terms from English into Albanian. The research focuses on the period from March 1, 2020, to July 27, 2020, which coincided with the global COVID-19 outbreak. 30 COVID-19-related terms in English and their Albanian equivalents were examined for this purpose. Data for this research was collected from two primary sources: the COVID-19 Terminology Collection from the European Union Terminology Database (IATE) and the Albanian equivalents obtained from news reports published by the healthcare authorities on the Ministry of Health and Social Protection of Albania’s website. The study employed several theoretical frameworks to analyze the translation strategies. Vin and Darbelnet’s translation model, the sociolinguistic model, and the metaphor translation method were utilized to achieve the research objectives. Vin and Darbelnet’s model provided a structured approach to analyzing translation techniques, such as borrowing, calque, literal translation, transposition, modulation, equivalence, and adaptation. The sociolinguistic model helped to understand how social and cultural factors influenced the choice of terminology and its reception by the public. The metaphor translation method was particularly relevant given the widespread use of metaphorical language in describing the pandemic and its effects. The findings offer insights into the most effective translation methods for accurately conveying selected COVID-19 terms in Albanian while preserving the intended stylistic essence of the original terms. The research emphasizes the importance of making controlled linguistic choices during translation rather than freely creating and adopting COVID-19 terminology for public use. Standardizing terminology is essential for clear and consistent communication, particularly during a public health crisis. The study highlights the potential risks of using inconsistent or poorly translated terms, which can lead to confusion, misinformation, and reduced public compliance with health guidelines. Furthermore, the research emphasizes the importance of making controlled linguistic choices during translation rather than freely creating and adopting COVID-19 terminology for public use.